Ontology Development for Medical and Health Science Domain in the Quran - Afifi Mohamad Safee, Muhammad; Mohd Saudi, Madihah; Saadan, Kamarudin (International Journal of Engineering and Technology, 2018)
Ontology is known as a knowledge representation and acts as a sharing platform for common ideas within a similar domain. It has a tree structure to ease the information presentation to users. Nowadays, it is very important to have a consistent and systematic way of presenting and retrieving different sources of knowledge such as the Quran and Hadith. Since there is so much useful information that can be retrieved from the Quran, especially for the Medical and Health Science domain, this paper presents the development of ontology for the Medical and Health Science domain in the Quran by adopting the Ontology 101 approach. These include the scope and domain determination, competency question formulation, ontology construction, and ontology evaluation. The proposed ontology in this paper has successfully retrieved the correct answers for Medical and Health Science using related queries via SPARQL-query and has been evaluated by the domain experts. Furthermore, the ontology structure accuracy has also been verified using reasoner, where it detected inconstancy during ontology development. For future work, this research paper can be used as a reference and basis to answer user queries, data integration with other applications or this ontology can be further expanded.Â Â